THE EFFECT OF FINANCIAL STATEMENTS DISCLOSURE ON FINANCIAL DISTRESS: A STUDY OF INFRASTRUCTURE COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE - Zufrizal (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2022)
This study examines the effect of the disclosure of financial statements on financial distress in infrastructure companies listed on the Indonesia Stock Exchange for the 2014-2018 period. The research used secondary data obtained from annual reports and financial statements of 19 infrastructure companies. The research utilized a quantitative approach by employing logistic regression analysis to determine the effect of financial statement disclosure on financial distress. The study found that financial statement disclosure has a significant negative effect on financial distress. This finding implies that companies that disclose their financial statements adequately have a lower likelihood of experiencing financial distress. Therefore, companies should prioritize the timely and accurate disclosure of financial information to reduce the risk of financial distress.